Phytochemical Composition, Antioxidant, and Antibacterial Activities of Macaranga peltata Leaf Extracts - THETCHINAMOORTHI RATHIMEENA,; SUBRAMANIAM KALIDASS, (The Bioscan, 2025)
This study aims to assess and compare the phytochemical profile, antioxidant potential, and antibacterial activity of various crude extracts derived from fresh Macaranga peltata leaves. The extracts were prepared using different organic solvents, including methanol, ethyl acetate and dimethyl sulfoxide (DMSO). Antioxidant activity was quantified using DPPH and superoxide anion radical scavenging assays, while antibacterial properties were tested using agar disc diffusion method. Phytochemical screening revealed that the methanolic extract showed more positive results compared to those obtained with ethyl acetate and DMSO extracts. In terms of antioxidant activity, the crude extracts followed the order: methanol > ethyl acetate > DMSO. Similarly, the methanolic extract demonstrated moderate antibacterial activity, outperforming the other two solvent extracts. Overall, the methanol extract exhibited the highest bioactivity among the solvents tested. GC-MS analysis of the methanolic extract identified twelve phytochemical constituents. In conclusion, crude extracts from fresh M. peltata leaves, especially those prepared with methanol, show promise as potential sources of new antioxidant and antibacterial agents.